Prisoners and their children: An innovative model of 'whole family' support. (December 2017) - Clancy, Anna; Maguire, Mike
The article reports key findings from an evaluation of 'Invisible Walls Wales' (IWW), a multi-agency 'through the gate' project in HMP Parc, South Wales, based on an innovative model of 'whole family' support for prisoners, their children and partners. It provides an overview of previous research on the impact of parental imprisonment on children and families, including financial hardship, emotional stress and risks of 'intergenerational offending'. It outlines the core elements of the IWW model and the substantial infrastructure of family support facilities in the prison on which it was built. It summarises outcomes of the project for fathers, partners and children, and gives examples of how IWW's 'whole family' approach is influencing policy and practice elsewhere. Reoffending rates are not yet available, but are anticipated to be low. However, the key strength of the project, it is argued, lies in its emphasis on the 'whole family' as the main beneficiary, rather than focusing narrowly on rehabilitation of the father.